Mal-angulation of femoral rotational osteotomies causes more postoperative sagittal mechanical leg axis deviation in supracondylar than in subtrochanteric procedures - Jud, Lukas (J Exp Orthop, 2020)
PURPOSE: Alteration of the postoperative frontal mechanical leg axis is a known problem in femoral rotational osteotomies. However, the maintenance of the sagittal mechanical leg axis seems also important. Goal of this study was to investigate the impact of femoral rotational osteotomies on the sagittal mechanical leg axis and to identify the degree of mal-angulation of the osteotomy planes that alter the postoperative sagittal alignment relevantly. METHODS: Using 3D bone models of two patients with a pathologic femoral torsion (42° antetorsion and 6° retrotorsion), subtrochanteric and supracondylar rotational osteotomies were simulated first with an osteotomy plane perpendicular to the mechanical femoral axis (baseline osteotomy plane), second with predefined mal-angulated osteotomy planes. Subsequently, five different degrees of rotation were applied and the postoperative deviations of the sagittal mechanical leg axes were analyzed. RESULTS: Using the baseline osteotomy plane, the sagittal mechanical leg axis changed by 0.4° ± 0.5° over both models. Using the mal-angulated osteotomy planes, maximum deviation of the sagittal mechanical leg axis of 4.0° ± 1.2° and 11.0° ± 2.0° was observed for subtrochanteric and for supracondylar procedures, respectively. Relevant changes of more than 2° were already observed with mal-angulation of 10° in the frontal plane and 15° of rotation in supracondylar procedures. CONCLUSION: Relevant changes of the postoperative sagittal mechanical leg axis could be observed with just slight mal-angulation of the osteotomy planes, in particular in supracondylar procedures and in cases with higher degrees of rotation. However, osteotomies perpendicular to the femoral mechanical axis showed no relevant alterations.